Development of key indicators of hospital resilience: a modified Delphi study. (April 2015) - Zhong, Shuang; Clark, Michele; Hou, Xiang-Yu; Zang, Yuli; FitzGerald, Gerard
Objectives: Hospital resilience is an emerging concept, which can be defined as 'a hospital's ability to resist, absorb, and respond to the shock of disasters while maintaining its critical health care functions, and then recover to its original state or adapt to a new one'. Our aim was to develop a comprehensive framework of key indicators of hospital resilience. Methods: A panel of 33 Chinese experts was invited to participate in a three-round, modified Delphi study to develop a set of potential measures previously derived from a literature review. In the first round, these potential measures were modified to cover the comprehensive domains of hospital resilience. The importance of proposed measures was scored by experts on a five-point Likert scale. Subsequently, the experts reconsidered their voting in light of the previous aggregated results. Agreement on measures was defined as at least 70% of the responders agreeing or strongly agreeing to the inclusion of a measure. Results: A large proportion of preliminary measures (89.5%) were identified as having good potential for assessing hospital resilience. These measures were categorized into eight domains, 17 subdomains, and 43 indicators. The highest rated indicators (mean score) were: equipment for on-site rescue (4.7), plan initiation (4.6), equipment for referral of patients with complex care needs (4.5), the plan execution (4.4), medication management strategies (4.4), emergency medical treatment conditions (4.4), disaster committee (4.4), stock types and quantities for essential medications (4.4), surge capacity of emergency beds (4.4), and mass-casualty triage protocols (4.4). Conclusions: This framework identifies a comprehensive set of indicators of hospital resilience. It can be used for hospital assessment, as well as informing priority practices to address future disasters better.